Malaysian students’ perceptions of flipped classroom: a case study - Zainuddin, Z.; Attaran, M. (Taylor & Francis, 2016)
The purpose of this study was to evaluate a class in University of Malaya where flipped learning was applied, and to examine students’ perceptions and feedback towards flipped classroom. Data were collected using both quantitative and qualitative methods, i.e. survey, focus group and individual interviews. The results indicated that most students had positive perceptions towards the use of flipped classroom and most of them would recommend flipped learning for other courses and other students. Regarding students’ feedback, most of them suggested that flipped video provided on the SPeCTRUM website should become more engaging and shorter, and should be situated within an authentic context. Also, flipped learning generated positive impacts for shy and quiet students, international students who were not fluent in English language and full-time students who had more time for learning. However, part-time students faced a challenge in flipped classroom due to lack of time to participate and become familiar with the content before attending the class.